Head Trauma in Paediatric Patients Referring to a Spoke Hospital - Ragusa, Neftj; Deut, Virginia; Luotti, Diego; Depaoli, Alessandro; Berger, Massimo (International Journal of Pediatrics and Child Health, 2024)
Introduction: Head trauma (HT) is a leading cause of morbidity and mortality in children worldwide. The primary aim of this study was to describe patients presenting to our first-level Emergency Department (ED) following a HT. The secondary aims were to compare both the epidemiology and the management of paediatric patients with literature data, analyzing the appropriateness of management of children’s traumatic brain injuries according to the current guidelines. Methods: We conducted a retrospective review of medical records of patients aged < 14 years who attended our first-level ED due to head trauma from July 1, 2021, and June 30, 2022. Clinical data, including age, gender, injury mechanism, location of trauma, time from traumatic event and ED arrival, symptoms at first evaluation, physical examination findings, radiological investigation results, medications administered in ED and prescribed at home, and outcome were collected and compared with data available in literature and current guidelines. Results: A total of 117 children aged < 14 years who attended our first-level ED due to head trauma from July 1, 2021, and June 30, 2022, were analyzed. Most of them were males aged 1-3 years. Frontal bone was the commonest side of trauma (43% of HT). Only eleven patients (9%) had a brain CT scan and 4 of them showed pathological findings. None had signs of bleeding. Four of the patients were transferred to a HUB hospital, provided with a paediatric neurosurgery and more important none of them has developed neurological sequelae or death. Discussion: Our 1-year observation of HT showed how this is a frequent indication for ED referral, especially in young children. In our hands less than 10% of cases required CT scan that reported pathological cases in 4 patients only (3%). We can conclude that the reduction of ionizing radiation exposition can be obtained with skilled experienced physicians.